2017
DOI: 10.1590/0037-8682-0371-2016
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and antimicrobial susceptibility of non-fermenting Gram-negative bacilli isolated from clinical samples at a tertiary care hospital

Abstract: Introduction:We compared the prevalence and antimicrobial susceptibility of non-fermenting gram-negative bacilli (NFGNB) isolated from clinical samples at a Brazilian tertiary care hospital in 2008 and 2013. Methods: Collected data included patient's name, age, sex, inpatient unit, laboratory record number, type of biological material, culture test result, and antimicrobial susceptibility of isolated strains. Results: Out of 19,112 culture tests analyzed, 926 (4.8%) were positive for NFGNB. Among these, 45.2% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…It seems that the high pressure of antibiotics due to greater empirical or indiscriminate use of antibiotics can lead to carbapenem resistance in the hospital setting. Moreover, consistent with our study, a large outbreak of MBL-producing NFGNB infections, especially due to A. baumannii isolates were described in India ( 8 , 9 ), Brazil ( 1 ), Pakistan ( 32 ), and Nepal ( 33 ). In the present study, it was found that 33.3% and 46.7% of carbapenem-resistant P. aeruginosa isolates, and 13.3% and 28.9% of carbapenem-resistant A. baumannii isolates were harboring bla IMP-1 and bla VIM-1 genes, respectively.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…It seems that the high pressure of antibiotics due to greater empirical or indiscriminate use of antibiotics can lead to carbapenem resistance in the hospital setting. Moreover, consistent with our study, a large outbreak of MBL-producing NFGNB infections, especially due to A. baumannii isolates were described in India ( 8 , 9 ), Brazil ( 1 ), Pakistan ( 32 ), and Nepal ( 33 ). In the present study, it was found that 33.3% and 46.7% of carbapenem-resistant P. aeruginosa isolates, and 13.3% and 28.9% of carbapenem-resistant A. baumannii isolates were harboring bla IMP-1 and bla VIM-1 genes, respectively.…”
Section: Discussionsupporting
confidence: 91%
“…Non-fermentative Gram-negative bacilli have emerged as a significant cause of healthcare-associated infections. The ever-increasing emergence of antibiotic resistance in NFGNB and the lack of new antibacterial agents is a major challenge for treating patients suffering from infections caused by them ( 1 , 23 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Alterations of chromosomal genes are still by far the most critical mechanisms of β-lactam resistance in NFGNBs, although transferable carbapenem resistance is becoming increasingly important 1 .…”
Section: Discussionmentioning
confidence: 99%